WORKLOAD DYNAMICS AND ORGANIZATIONAL SUPPORT: THEIR IMPACT ON JOB STRESS AND EMPLOYEE COMMITMENT AT BANK ABC REGION X - Siti Hidajati Ramdani; Theresia Agitha Dewi; Susi Adiawaty (ESENSI: Jurnal Manajemen Bisnis, 2025)
This study aims to analyze the influence of Workload and Perceived Organizational Support (POS) on Job Stress and their impact on Organizational Commitment at Bank ABC, Region X. High workload and lack of organizational support can trigger job stress, which negatively impacts employee commitment. This study used a quantitative approach with the Partial Least Squares (PLS) method to analyze the relationship between variables. The study sample consisted of 54 employees of Bank ABC, Region X, selected using a saturated sampling technique (non-probability sampling). The results showed that workload had a significant positive effect on job stress, while perceived organizational support had a significant effect on job stress, which is theoretically negative. Furthermore, job stress was shown to have a significant negative impact on employee commitment to the organization. Simultaneously, workload, POS, and job stress strongly explained variations in organizational commitment ($R^2=0.989). This study emphasizes the importance of effective workload management and increased organizational support in efforts to improve employee well-being and commitment, with job stress playing a significant role as a mediating variable.